33=3(3+q)

Simple and best practice solution for 33=3(3+q) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 33=3(3+q) equation:



33=3(3+q)
We move all terms to the left:
33-(3(3+q))=0
We add all the numbers together, and all the variables
-(3(q+3))+33=0
We calculate terms in parentheses: -(3(q+3)), so:
3(q+3)
We multiply parentheses
3q+9
Back to the equation:
-(3q+9)
We get rid of parentheses
-3q-9+33=0
We add all the numbers together, and all the variables
-3q+24=0
We move all terms containing q to the left, all other terms to the right
-3q=-24
q=-24/-3
q=+8

See similar equations:

| 32=w*4 | | 6x+5-2x=x+14 | | y/3+4=13 | | 3x+6+5x-4=11 | | -v+278=127 | | x3=249 | | 3x+6+5x-4=39 | | 271-v=88 | | 2(6x+18)=48 | | (x+14)x(4x-9)=180 | | 1/7m-6=3/7m+4 | | 95,000=10,000(1.08)2x | | 5(5+u)=50 | | -1.8+x=1.6 | | 8x=7-15x | | 8^x+2^3x-1=96 | | 4v-4+(5v-5)=180 | | x+x+20+x+20+130-x=360 | | 4(6m+5)-7m=-116 | | 2m-10+5m=45 | | 2(6x+9=5(7x+10 | | 0,81*x=8 | | 6(x-3)-2x=74 | | 7=n/5-4 | | 1x-0.3x=10 | | 2(4x-1)=5.2x+17-8 | | (2x+21)+(3x+16)+(5x-3)=100 | | 44+u=76 | | 60°=(7x+25) | | 2(3x-4)=2x-8+4x | | x-30+4x=70 | | 9=z-11 |

Equations solver categories